2021
DOI: 10.1111/tpj.15580
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis SKU5 Similar 11 and 12 play crucial roles in pollen tube integrity, growth and guidance

Abstract: SUMMARY Pollen tube integrity, growth and guidance are crucial factors in plant sexual reproduction. Members of the plant Skewed5 (SKU5) Similar (SKS) family show strong similarity to multicopper oxidases (MCOs), but they lack conserved histidines in MCO active sites. The functions of most SKS family members are unknown. Here, we show that Arabidopsis pollen‐expressed SKS11 and SKS12 play important roles in pollen tube integrity, growth and guidance. The sks11sks12 mutant exhibited significantly reduced male f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The SKS family counts 19 members in Arabidopsis ( Sedbrook et al 2002 ). A recent study indicated that mutating the last histidine residue in the copper center of SKS11 produced a protein with enough activity to rescue the defects of the sks11 sks12 double mutant ( Duan et al 2021 ). We, therefore, suspect that some SKS proteins may have evolved new functions that do not require their copper cofactor, while others like SKS18 behave as AAOs and rely on copper stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SKS family counts 19 members in Arabidopsis ( Sedbrook et al 2002 ). A recent study indicated that mutating the last histidine residue in the copper center of SKS11 produced a protein with enough activity to rescue the defects of the sks11 sks12 double mutant ( Duan et al 2021 ). We, therefore, suspect that some SKS proteins may have evolved new functions that do not require their copper cofactor, while others like SKS18 behave as AAOs and rely on copper stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ZmSKS13 influences kernel development through modulating ROS homeostasis ( Zhang et al 2021 ). In Arabidopsis, SKS11 and SKS12 are required for pollen tube integrity, growth, and guidance by regulating ROS levels ( Duan et al 2021 ). Pollen-expressed SKS13 affects pollination/fertilization ( Ji et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the roles of ROS in seed dormancy and germination have been extensively studied (Bailly, 2019), less attention has been given to the maintenance of ROS homeostasis during seed development. Zhang et al (2021b) (Chen et al, 2014a;Duan et al, 2022). Therefore, further investigations are needed to understand how SKS proteins modulate ROS levels in opposite manners.…”
Section: Ros Overaccumulation Leads To Defective Kernelsmentioning
confidence: 99%
“…SKS proteins in Arabidopsis also function in ROS homeostasis. Whereas AtSKS1 functions in ROS scavenging in a manner similar to ZmSKS13 (Chen et al, 2023), AtSKS11, AtSKS12, and AtSKS13, in contrast with ZmSKS13, promote ROS production (Chen et al, 2014a; Duan et al, 2022). Therefore, further investigations are needed to understand how SKS proteins modulate ROS levels in opposite manners.…”
Section: Roles Of Ros In Maize Developmentmentioning
confidence: 99%
“…As the ectopic "SI-like PCD" response in Arabidopsis roots 25 also requires AtPGAP1, it appears that broadly expressed GPI-APs, rather than those specifically involved in reproduction, are involved in SI. Interestingly, SKU5, which regulates directional root growth, is a member of a gene family containing pollen-expressed SKS11/12, which control pollen tube growth 54 . As well as playing a key role in cell-cell signaling during reproduction and development, GPI-APs also participate in pathogen responses 37,47,55 .…”
Section: Implication Of a Potential Role For Gpi-aps In Cell-cell Sig...mentioning
confidence: 99%